2021
DOI: 10.1016/j.mechmachtheory.2021.104249
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design and comparative study of two antagonistically actuated tensegrity joints

Abstract: This paper proposes design strategies and a comparative study of two antagonistically actuated tensegrity joints: a revolute (R) joint and an anti-parallelogram (X) joint. Geometrically, the R-joint has a fixed center of rotation while the X-joint has a moving center of rotation. Both joints are equipped with two lateral springs and are actuated by cables passing through these springs. Such tensegrity joints can be of interest for developing lightweight manipulators. They are designed to reach a prescribed wre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…The same behavior was also reported for a 2R joint with offsets that represents one circle pure rolling over another [12]. In contrast, for an anti-parallelogram joint, that is equivalent to one ellipse pure rolling over another, the antagonistic actuation has a positive influence on the joint stiffness [11], just as in the biological joints. Thus, drawing inspiration from the anti-parallelogram mechanism, the goal of this work is to find all the four-bar mechanisms with symmetric limbs, that exhibit an increase in stiffness with antagonistic actuation by cables.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The same behavior was also reported for a 2R joint with offsets that represents one circle pure rolling over another [12]. In contrast, for an anti-parallelogram joint, that is equivalent to one ellipse pure rolling over another, the antagonistic actuation has a positive influence on the joint stiffness [11], just as in the biological joints. Thus, drawing inspiration from the anti-parallelogram mechanism, the goal of this work is to find all the four-bar mechanisms with symmetric limbs, that exhibit an increase in stiffness with antagonistic actuation by cables.…”
Section: Introductionsupporting
confidence: 71%
“…There are other joints where stiffness modulation can be achieved without in-series springs, by only varying the cable forces, see e.g., the tensegrity-inspired joints presented in [11]. It was found that with the increase in antagonistic cable forces, the revolute joint experiences a drop in stiffness, which was a counterintuitive result [11].…”
Section: Introductionmentioning
confidence: 99%
“…As compared with simple revolute joints, X-joints do not have a fixed rotation axis, a common feature in biological joints [21,9]. Moreover, they have a number of advantages such as larger rotation ranges [4] and larger variations of stiffness [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is necessary to prepare for possible failures in the geared rolling units. Rolamite using flexures or X-joints using an anti-parallelogram, which can transmit a large torque, can be considered as a replacement for the gears [9,19]. On the other hand, it is required to verify experimentally whether the X-joint mechanism can be applied without modifying the existing cable actuation [20,21].…”
Section: Discussionmentioning
confidence: 99%